PERAN PENDIDIKAN DALAM MENYIKAPI ISU-ISU MULTIKULTURALISME DI INDONESIA - Rahayu, Febri Puja (Cahaya Ilmu Bangsa, 2025)
AbstractMulticulturalism is an integral part of cultural diversity in Indonesia, which consists of various tribes, religions and ethnicities. Education plays a vital role in addressing the challenges that arise from this diversity and in promoting social harmony. This article explores how education can effectively contribute to addressing issues of multiculturalism in Indonesia. By analyzing various educational approaches that can be implemented, the article highlights the importance of inclusive curricula, adequate teacher training and extracurricular activities that support cross-cultural understanding. It also emphasizes the important role of government policy in ensuring that the education provided to the younger generation is able to instill values of tolerance, mutual respect and social solidarity. Through comprehensive and holistic education, it is hoped that Indonesia's young generation will be able to coexist peacefully and productively in a multicultural society. Keywords: Education, Multiculturalism, Tolerance.AbstrakMultikulturalisme merupakan bagian integral dari keberagaman budaya di Indonesia yang terdiri dari berbagai suku, agama, dan etnis. Pendidikan memainkan peran vital dalam mengatasi tantangan yang muncul dari keberagaman ini dan dalam mempromosikan keharmonisan sosial. Artikel ini mengeksplorasi bagaimana pendidikan dapat berkontribusi secara efektif dalam menyikapi isu-isu multikulturalisme di Indonesia. Dengan menganalisis berbagai pendekatan pendidikan yang dapat diterapkan, artikel ini menyoroti pentingnya kurikulum inklusif, pelatihan guru yang memadai, serta kegiatan ekstrakurikuler yang mendukung pemahaman lintas budaya. Ditekankan pula peran penting dari kebijakan pemerintah dalam memastikan bahwa pendidikan yang diberikan kepada generasi muda mampu menanamkan nilai-nilai toleransi, saling menghargai, dan solidaritas sosial. Melalui pendidikan yang komprehensif dan holistik, diharapkan generasi muda Indonesia mampu hidup berdampingan secara damai dan produktif dalam masyarakat yang multikultural. Kata kunci: Pendidikan, Multikulturalisme, Toleransi.